Preparation and Characterization of Thermally Stable Collagens from the Scales of Lizardfish (Synodus macrops) - Junde Chen; Guangyu Wang; Yushuang Li (Marine Drugs, 2021)
Marine collagen is gaining vast interest because of its high biocompatibility and lack of religious and social restrictions compared with collagen from terrestrial sources. In this study, lizardfish (Synodus macrops) scales were used to isolate acid-soluble collagen (ASC) and pepsin-soluble collagen (PSC). Both ASC and PSC were identified as type I collagen with intact triple-helix structures by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and spectroscopy. The ASC and PSC had high amino acids of 237 residues/1000 residues and 236 residues/1000 residues, respectively. Thus, the maximum transition temperature (Tmax) of ASC (43.2 °C) was higher than that of PSC (42.5 °C). Interestingly, the Tmax of both ASC and PSC was higher than that of rat tail collagen (39.4 °C) and calf skin collagen (35.0 °C), the terrestrial collagen. Solubility tests showed that both ASC and PSC exhibited high solubility in the acidic pH ranges. ASC was less susceptible to the “salting out” effect compared with PSC. Both collagen types were nontoxic to HaCaT and MC3T3-E1 cells, and ASC was associated with a higher cell viability than PSC. These results indicated that ASC from lizardfish scales could be an alternative to terrestrial sources of collagen, with potential for biomedical applications.